2016
DOI: 10.1016/j.celrep.2016.03.071
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecules Facilitate Single Factor-Mediated Hepatic Reprogramming

Abstract: Recent studies have shown that defined factors could lead to the direct conversion of fibroblasts into induced hepatocyte-like cells (iHeps). However, reported conversion efficiencies are very low, and the underlying mechanism of the direct hepatic reprogramming is largely unknown. Here, we report that direct conversion into iHeps is a stepwise transition involving the erasure of somatic memory, mesenchymal-to-epithelial transition, and induction of hepatic cell fate in a sequential manner. Through screening f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 40 publications
3
92
1
1
Order By: Relevance
“…Some of the theoretical advantages of direct reprogramming strategies include the use of less time-consuming protocols, avoidance of the pluripotency stage and generation of cells with increased maturation profile for personalized medicine applications [3]. In fact, iHEPs were generated by direct reprogramming and were shown to be amenable for in vitro expansion and able to repopulate the liver when transplanted into mice [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the theoretical advantages of direct reprogramming strategies include the use of less time-consuming protocols, avoidance of the pluripotency stage and generation of cells with increased maturation profile for personalized medicine applications [3]. In fact, iHEPs were generated by direct reprogramming and were shown to be amenable for in vitro expansion and able to repopulate the liver when transplanted into mice [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
“…The significant presence of Klf4 in the regulation of DEGs and DE-TFs (Fig 2A and Fig 4A and 4B) supports the fact that Klf4 can be used as a candidate factor to increase the efficiency of the induction of hepatic fate from fibroblasts. For example, interestingly, Lim et al (2016) showed that using Klf4 and Myc in combination with hepatic-specific factors led to a significant increase in the efficiency of the generation of iHeps from fibroblasts [28]. Also, this study showed Klf4 and Myc are not crucial for the induction hepatocyte-like cells but increase the efficiency of the process.…”
Section: Discussionmentioning
confidence: 65%
“…Lim et al (2016) used a combination of Klf4 and Myc as their Yamanaka TFs along with Hnf4a as their hepatic-specific factor to drive the direct conversion of fibroblasts into iHeps. This group was also able to obtain iHeps from fibroblasts by combining small molecules with Hnf4a [28]. Despite the extensive use of TFs for the generation of hepatocyte-like cells through direct reprogramming, the molecular mechanisms by which different TFs regulate the gene expression program have not been well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several methods relying fully or partially on drug treatment to enhance cell conversion have emerged 12 . Many of these use fibroblasts as the starting cell type, reprogrammed towards pluripotency 13,14 or trans-differentiated to specialized cell types including neurons 15 , endothelial cells 16 , pancreatic like cells 17 , cardiomyocytes 18 , hepatocytes 19 or other cell types 20,21,22 . Such studies provide a proof of principle for drug-based reprogramming, the exact mechanisms of which, however, are often poorly understood, making extensive trial-and-error unavoidable.…”
Section: Introductionmentioning
confidence: 99%